ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MAEMATIKA DI KELAS V SD NEGERI 41 LUBUKLINGGAU - Septiyana, Eva; Sukasno; Hajani, Tri Juli (Unversitas Katolik Santo Thomas, 2022)
This writing aims to find out the types and factors of difficulty that students do in solving math story problems and to find out how to overcome students' difficulties in solving math story problems. The method used for this writing is a qualitative method of analysis type. The writing subject was taken by the fifth grade students of SD Negeri 41 Lubuklinggau with a total of 22 students. Collecting data in this paper using observation techniques, test questions, interviews and documentation. Data analysis techniques used in this paper are data reduction, data presentation and drawing conclusions. The results of the writing show that the types of difficulties experienced by students in solving math story problems are: 1). Difficulty transforming the problem, 2) difficulty using arithmetic operations, 3) difficulty drawing conclusions and 4) students are not careful in working on the questions. Factors causing difficulties in solving math story problems are 1) internal factors include: intellectual, interest and motivation. External factors include: school facilities and infrastructure. solutions to overcome difficulties include: students must understand the problem, students understand the mathematical model, students do a lot of exercises and students check answers again. The proportion of students' difficulties in solving problems with the number of students 22 people for the difficulty of transforming the problem is 16.6%, the difficulty using arithmetic operations is 27.8%, the difficulty in drawing conclusions is 72.2 and students are not careful in working on the problem of 67.7% .